Naringenin attenuates CCl4‐induced hepatic inflammation by the activation of an Nrf2‐mediated pathway in rats. (June 2014) - Esmaeili, Mohammad Ali; Alilou, Mostafa
Summary The possible protective effects of naringenin, a naturally occurring citrus flavonone, on carbon tetrachloride (CCl4)‐induced liver injury in rats and the mechanism underlying its effects were investigated. Forty rats were divided into five groups. Rats in Groups I and II served as the normal and injured liver groups, respectively; Group III rats were treated with the standard drug silymarin as a positive control; and rats in Groups IV and V (naringenin‐treated groups) were administrated 50 mg/kg, p.o., naringenin for 7 days. Liver samples were collected to evaluate mRNA and protein expression, histological changes and oxidative stress. Naringenin inhibited lipid peroxidation and reduced serum levels of hepatic enzymes induced by CCl4. In addition, naringenin increased the liver content of reduced glutathione and the activity of anti‐oxidant enzymes in rats treated with CCl4. Naringenin attenuated liver inflammation by downregulating CCl4‐induced activation of tumour necrosis factor (TNF)‐α, inducible nitric oxide synthase (iNOS) and cyclo‐oxygenase (COX‐2) at both the protein and mRNA levels. Naringenin treatment significantly increased NF‐E2‐related factor 2 (Nrf2) and heme oxygenase (HO‐1) expression in injured livers. In rats treated with CCl4 alone, decreases were seen in nuclear Nrf2 expression and in the mRNA levels of its target genes (e.g. HO‐1, NQO1 and glutathione S‐transferase alpha 3 (GST‐a3)). Together, the results suggest that naringenin can protect the liver against oxidative stress, presumably by activating the nuclear translocation of Nrf2 as well as attenuating the TNF‐α pathway to elicit an anti‐inflammatory response in liver tissue.